The Post-Corporate World Life After Capitalism - Korten, David C.; Korten, David C. (Berrett-Koehler Publishers, 1999)
- From the bestselling author of When Corporations Rule the World - An extensively researched, powerfully argued, eye-opening critique of how today's corporate captialism is destroying the things of real value in the world-like cancer destroys life - Portrays a hopeful future-alternatives to a corporate-dominated and money-ruled world-in showing how to resore health to markets, democracy, and every day life - Offers practical suggestions for individuals who want to contribute to the process of change - Co-published with Kumarian Press There is a deep chasm between the promises of the new global capitalism and the reality of social breakdown, spiritual emptiness, and environmental destruction it is leaving in its wake. In this important book, David Korten makes a compelling and well-documented case that capitalism is actually delivering a fatal blow not only to life, but also to democracy and the market. Among his startling ideas: Capitalism is a pathology that commonly afflicts market economies in the absence of vigilant public oversight. Since the economy internal to a corporation is a planned economy, the current consolidation of economic control under a handful of global corporations is a victory for central planning-not the market economy. The alternative to the new global capitalism is a global system of thriving, healthy market economies that function as extensions of healthy local ecosystems to meet the livelihood needs of people and communities. Radical as such proposals may seem, they actually reflect processes that are steadily gaining momentum around the world. The Post-Corporate World provides a vision of what's needed and what's possible, as well as a detailed agenda for change. Korten shows that to have a just, sustainable and compassionate society, concentrated absentee ownership and footloose speculative capital as embodied in the global, for-profit public corporation must be eliminated in favor of enterprises based on patient, rooted, stakeholder ownership limited to those who have a stake in the firm as a worker, supplier, customer, or member of the community in which it is located. Korten outlines numerous specific actions to free the creative powers of individuals and societies through the realization of real democracy, the local rooting of capital through stakeholder ownership, and a restructuring of the rules of commerce to create "mindful market" economies that combine market principles with a culture that nurtures social bonding and responsibility. Like Korten's previous bestseller, When Corporations Rule the World, this provocative book is sure to stimulate national dialogue and debate and inspire a bevy of grassroots discussions and initiatives. The Post-Corporate World presents readers with a profound challenge and an empowering sense of hope.